THE EFFECT OF WORKLOAD ON BANK EMPLOYEE PERFORMANCE IN MAKASSAR CITY - Faisal Tasbih; Yunus Amar; Nurdjanah Hamid (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2023)
The banking sector is currently required to play an active role in efforts to increase economic growth and improve people's lives. Human resource management must always be considered because it functions efficiently, effectively and productively to achieve company goals. One of the most crucial assets of a bank is employee performance. Consequently, human resources are required to always be able to develop themselves proactively in producing good performance. One of the causes of the poor performance produced by employees is the high workload that must be borne. This is due to a mismatch between the employees themselves and the work they are doing resulting in excessive workload. This study aims to analyze the effect of workload on the performance of bank employees. The research method uses a cross-sectional study design. The research began in May 2023 at a bank in Makassar City. The number of samples used were 106 employees who were taken using the total sampling technique. The collection of employee workload data and employee performance data was measured using a questionnaire with a Likert scale which was filled in directly by the respondents. Data were analyzed using the Chi-Square test. Chi-Square test results show that the workload variable is significantly related to employee performance (p<0.05). The company (bank) must pay serious attention to the workload given to employees.